Prevalence of Helicobacter pylori antibiotic resistance pattern in Malaysia - Teh, X.S.; Khosravi, Y.; Gunaletchumy, S.P.; Ramli, N.S.K.; Loke, M.F.; Goh, K.L.; Vadivelu, J. (2012)
Helicobacter pylori is well-known for its high genomic diversity and rapid genetic mutation by both natural transformation and inter-or intra-species conjugation. Therefore, eradication of H. pylori will be made difficult when antibiotic resistence was developed towards current treatment regimen. Although previous studies had shown low resistence rate towards major antibiotics such as clarithromycin, levofloxcin, amoxicillin and tetracycline in the Malaysian population, increasing migration of foreign workers might disrupt the gene pool.